Outcomes of Congenital Diaphragmatic Hernia in One of the Twins - Wang, Weipeng; Pan, Weihua; Chen, Jie; Xie, Wei; Liu, Ming; Wang, Jun (American Journal of Perinatology, 2019)
Objective Congenital diaphragmatic hernia (CDH) occurred in one of the twins is rarely seen. This study aims to describe the clinical features and outcomes of this special CDH.Study Design The medical records of all CDH neonates treated in our institution between 2010 and 2016 were retrospectively reviewed. Data were analyzed using parametric and nonparametric tests, appropriately. Association between the twin pregnancy and outcomes was assessed.Results Eighty-nine patients met the inclusion criteria. In the multivariate analysis, liver herniation, observed/expected lung-to-head circumference ratio, and lower birth weight were independently related to the survival rate of CDH. Eleven patients were identified with CDH occurred in only one of the twins. Among them, seven patients (63.6%) were premature and six (54.5%) were found with low birth weight. Compared with CDH patients with singleton pregnancy, they had significantly higher rates of prematurity (p < 0.001) and lower birth weight (p < 0.001). Additionally, they had worse outcomes with a shorter duration of mechanical ventilation (p = 0.015) and lower survival rate at discharge (p = 0.024).Conclusion Preterm birth and low birth weight are more common in CDH patients with twin pregnancy, which may lead to worse outcomes.
Keywords: congenital diaphragmatic hernia; twins; preterm birth; low birth weight; outcome